Hsp90 is involved in the entry of clostridial neurotoxins into the cytosol of nerve terminals. (4th August 2016) - Azarnia Tehran, Domenico; Pirazzini, Marco; Leka, Oneda; Mattarei, Andrea; Lista, Florigio; Binz, Thomas; Rossetto, Ornella; Montecucco, Cesare
Summary: Botulinum and tetanus neurotoxins are the most toxic substances known and form the growing family of clostridial neurotoxins. They are composed of a metalloprotease light chain (L), linked via a disulfide bond to a heavy chain (H). H mediates the binding to nerve terminals and the membrane translocation of L into the cytosol where their substrates, the three SNARE proteins, are localised. L translocation is accompanied by unfolding, and it has to be reduced and reacquire the native fold to exert its neurotoxicity. The Thioredoxin reductase–Thioredoxin system is responsible for the reduction, but it is unknown whether the refolding of L is spontaneous or aided by host chaperones. Here we report that geldanamycin, a specific inhibitor of heat shock protein 90, hampers the refolding of L after membrane translocation and completely prevents the cleavage of SNAREs. We also found that geldanamycin strongly synergises with PX‐12, an inhibitor of thioredoxin, suggesting that the processes of L chain refolding and interchain disulfide reduction are strictly coupled. Indeed we found that the heat shock protein 90 and the Thioredoxin reductase–Thioredoxin system physically interact on synaptic vesicle where they orchestrate a chaperone‐redox machinery which is exploited by clostridial neurotoxins to deliver their catalytic part into the cytosol.